FACTORS INFLUENCING THE USE OF E-LEARNING IN PUBLIC UNIVERSITIES IN KENYA - Njuguna, George; Nzuve, Snm (European Journal of Technology, 2017)
Purpose: The purpose of the study was to determine the factors influencing the use of e-learning in Public Universities in Kenya. Methodology: A descriptive survey design was used in finding out the factors influencing the use of e-learning in Public universities in Kenya. The Population of this study will be the 19,205 employees (Academic and non-Academic staff) in all public universities. The sample size was 96 employees. A questionnaire was the preferred data collection instrument for this study. Descriptive and inferential statistics were used. Results: Results revealed perceived usefulness was important in explaining the use of e-learning. This is supported by a p value 0.000 which means that perceived usefulness is a statistically significant predictor of the use of e-learning. Results further revealed that such perceived ease of use is important in determining use of e-learning as demonstrated by a p value of 0.000. Analysis showed that supporting infrastructure is a key determinant in use of e-learning in Kenyan universities and this was supported by a correlation coefficient of 0.398 Unique contribution to theory, practice and policy: The universities should ensure that e-learning saves time compared to face to face learning. They should also be in such a position that ensures that e-Learning saves money compared to face to face learning for the students.